Germs in the Family: The Short- and Long-Term Consequences of Intrahousehold Disease Spread - Daysal, N. Meltem; Ding, Hui; Rossin-Slater, Maya; Schwandt, Hannes (American Economic Review, 2026)
Preschool-aged children get sick frequently and spread disease to other family members. Despite the universality of this experience, there is limited causal evidence on the magnitudes and consequences of these externalities, especially for infant siblings with developing immune systems and brains. We show in Danish administrative data that during infancy, younger siblings have two to three times higher hospitalization rates for respiratory conditions than older siblings. We combine birth order and within-municipality variation in respiratory disease prevalence among young children, finding lasting differential impacts of early-life respiratory disease exposure on younger siblings' earnings, educational attainment, chronic respiratory health, and mental health-related outcomes. (JEL D13, D62, I12, J12, J13, J24, J31)